Chemical absorption process for degradation of VOC gas using heterogeneous gas-liquid photocatalytic oxidation: Toluene degradation by photo-Fenton reaction - Tokumura, M.; Nakajima, R.; Znad, Hussein; Kawase, Y. (Elsevier, 2008)
A novel process for degradation of toluene in the gas-phase using heterogeneous gas-liquid photocatalytic oxidation has been developed. The degradation of toluene gas by photo-Fenton reaction in the liquid-phase has experimentally examined. The photo-Fenton reaction in the liquid-phase could improve the overall toluene absorption rate by increasing the driving force for mass transfer and as a result enhance the removal of toluene in the exhaust gas. The toluene concentrations in the inlet gas were varied in the range from 0.0968 to 8.69 g m-3 with initial hydrogen peroxide concentration of 400 mg l-1 and Fe dose of 5.0 mg l-1. It was found that toluene in the inlet gas was almost completely dissolved into water and degraded in the liquid-phase for the inlet toluene gas concentration of less than 0.42 g m-3. The dynamic process of toluene gas degradation by the photo-Fenton reaction providing information for reaction kinetics and mass transfer rate was examined. Toluene removal kinetic analysis indicated that photo-Fenton degradation was significantly affected by H2O2 concentration. The experimental results were satisfactorily described by the predictions simulated using the simplified tanks-in-series model combined with toluene removal kinetic analysis. The present results showed that the proposed chemical absorption process using the photo-Fenton heterogeneous gas-liquid photocatalytic oxidation is very effective for degradation of volatile organic gases. © 2008 Elsevier Ltd. All rights reserved.